Commencement, 1973 (1973)
Ray Bennett, Chairman, Senior Week Gay Draxler, Poly Royal Queen Dean Chandler, Dean of Students Ken Ristow, Student Dan Winn, Chairman, Tree Planting Committee Robert E. Kennedy, Cal Poly President Jeanette Hiatt, on the Tree Planting Committee